(3cJGH GdMLL GdbhjI aj HjGf GdhUjIs
(3ChdgG (B:s
(3GdMeO ddg GdPi CQSd GdCfHjGA hHYO aEfg bO PcQ di HYV GdaVdGA GdUGdMjf GdMLI GdChdi dG jNai Ydi ef JJHY GdBKGQ hRhGd GdCNHGQ s
(3BNQgG (B:s
(3hEfeG EbJUQJ Ydi gPg GdCLhHI dCfgG Jbhe HGdcaGjI hJhUd Edi GdgOGjI hEdG aGdhGLHGJ hGdCMGOjK ZRjQI hdG jJSY GdhbJ EHQGRgG hdG Jbhe GdCbdGe HESJNQGLgG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs